Peak Bone Mass and Bone Microarchitecture in Adults Born With Low Birth Weight Preterm or at Term: A Cohort Study - Balasuriya, Chandima N. D.; Evensen, Kari Anne I.; Mosti, Mats P.; Brubakk, Ann-Mari; Jacobsen, Geir W.; Indredavik, Marit S.; Schei, Berit; Stunes, Astrid Kamilla; Syversen, Unni (The journal of clinical endocrinology and metabolism, 2017)
Peak bone mass (PBM) is regarded as the most important determinant of osteoporosis. Growing evidence suggests a role of intrauterine programming in skeletal development. We examined PBM and trabecular bone score (TBS) in adults born preterm with very low birth weight (VLBW) or small for gestational age (SGA) at term compared with term-born controls. This follow-up cohort study included 186 men and women (25 to 28 years); 52 preterm VLBW (≤1500 g), 59 term-born SGA (<10th percentile), and 75 controls (>10th percentile). Main outcome was bone mineral density (BMD) by dual x-ray absorptiometry. Secondary outcomes were bone mineral content (BMC), TBS, and serum bone markers. VLBW adults had lower BMC and BMD vs controls, also when adjusted for height, weight, and potential confounders, with the following BMD Z-score differences: femoral neck, 0.6 standard deviation (SD) (P = 0.003); total hip, 0.4 SD (P = 0.01); whole body, 0.5 SD (P = 0.007); and lumbar spine, 0.3 SD (P = 0.213). The SGA group displayed lower spine BMC and whole-body BMD Z-scores, but not after adjustment. Adjusted odds ratios for osteopenia/osteoporosis were 2.4 and 2.0 in VLBW and SGA adults, respectively. TBS did not differ between groups, but it was lower in men than in women. Serum Dickkopf-1 was higher in VLBW subjects vs controls; however, it was not significant after adjustment for multiple comparisons. Both low-birth-weight groups displayed lower PBM and higher frequency of osteopenia/osteoporosis, implying increased future fracture risk. The most pronounced bone deficit was seen in VLBW adults.